2013
DOI: 10.1038/modpathol.2012.145
|View full text |Cite
|
Sign up to set email alerts
|

High proliferation is associated with inferior outcome in male breast cancer patients

Abstract: Assessment of proliferation is important in female breast cancer and individual treatment decisions are based upon its results, especially in the luminal subgroups. Gene expression analyses fail to group male breast cancer into the intrinsic subgroups previously established in female breast cancer. Even though proliferation has been shown to divide male breast cancer into molecular subgroups with different prognoses, the clinical importance of proliferation markers has not yet been elucidated. Previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Patients forming the Swedish cohort were identified through the Swedish National Cancer Registry. 19 Males diagnosed between 1990 and 2007 within the Lund and UppsalaOrebro regions that had available formalin-fixed paraffin-embedded tumor blocks, clinicopathological data and outcome data were included in the study. This work was carried out with approval from the Peter MacCallum Cancer Center Ethics Committee (Project No: 11/61) and the local ethics committee in Uppsala, Sweden (i2007/254), and the Lund University (2012/89).…”
Section: Patient Accrualmentioning
confidence: 99%
“…Patients forming the Swedish cohort were identified through the Swedish National Cancer Registry. 19 Males diagnosed between 1990 and 2007 within the Lund and UppsalaOrebro regions that had available formalin-fixed paraffin-embedded tumor blocks, clinicopathological data and outcome data were included in the study. This work was carried out with approval from the Peter MacCallum Cancer Center Ethics Committee (Project No: 11/61) and the local ethics committee in Uppsala, Sweden (i2007/254), and the Lund University (2012/89).…”
Section: Patient Accrualmentioning
confidence: 99%
“…However, Wang-Rodriguez and colleagues found better survival in ER-positive patients but did not find a benefit from treatment with tamoxifen (8) (http://www.pubmed central.nih.gov/articlerender.fcgi?artidZ314449&toolZ pmcentrez -B8). Recently, a Sweden study has found that patients undergoing adjuvant endocrine treatment had a poorer breast cancer survival compared with those cases without such treatment (9). The distinct hormone signal in both genders may be the cause of their different responses to anti-hormonal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to male disease, female rates of ERα-and/or PR-positivity are higher (Giordano et al 2004, Nilsson et al 2013. Notably, AR is highly expressed in male breast cancers (Zhou et al 2014) and has been found to be indicative of good outcome in male breast (Shaaban et al 2012) and poor outcome in hormone-refractory prostate cancer (Buhmeida et al 2006).…”
Section: Molecular Featuresmentioning
confidence: 97%
“…Male breast cancer is rare, accounting for around 1% of all breast cancers (Siegel et al 2016) and is frequently positive for ERα (91-95%) and/or PR (80-81%) (Giordano et al 2004, Nilsson et al 2013). The most well-known anti-estrogenic therapy is tamoxifen, which competitively blocks estradiol binding to the receptor, effectively inducing an alternative conformation of ERα ligand-binding domain (Shiau et al 1998), which prevents the formation of an active transcription complex (Zwart et al 2007) and inhibiting the onset of tumor cell proliferation programs (Severson et al 2016).…”
Section: Introductionmentioning
confidence: 99%